Chromosomal localization of the Moloney sarcoma virus mouse cellular (c-mos) sequence. - Swan, D (1982)
The Moloney sarcoma virus-specific onc gene, referred to as v-mos, was used as probe to hybridize to restricted DNAs from various mouse-Chinese hamster hybrid cell lines. These hybrid cells contain, in addition to all of the Chinese hamster chromosomes, various numbers (less than a full complement) of mouse chromosomes. Comparison of the presence or absence of the mouse cellular mos gene with the known karyotype in each of the hybrid cell lines allows us to conclude that the mos gene is on mouse chromosome 4.